Diagnosis of Idiopathic Pulmonary Fibrosis “Pragmatic Challenges in Clinical Practice” - Tzilas, Vasilios; Tzouvelekis, Argyris; Chrysikos, Serafim; Papiris, Spyridon; Bouros, Demosthenes (Frontiers in Medicine, 2017)
The past few years have signaled a major breakthrough on the management of Idiopathic Pulmonary Fibrosis (IPF). Finally, we have drugs in our arsenal able to slow down the inexorable disease natural course. On the other hand, the latter evidence has increased the responsibility for a timely and accurate diagnosis. Establishment of IPF diagnosis, directly affects the choice of appropriate treatment. The current diagnostic guidelines represent a major step forward providing an evidence-based road map; yet, clinicians are encountering major diagnostic dilemmas that inevitably affect therapeutic decisions. This review article aims to summarize the current state of knowledge on the diagnostic procedure of IPF based on the current guidelines and discuss pragmatic difficulties and challenges encountered by clinicians with regards to their applicability in the everyday clinical practice.